2022-RA-1042-ESGO The prognostic impact of anaemia in cervical cancer patients treated with chemoradiation. (20th October 2022) - El-Modir, Ahmed; Fernando, Indrajit; Winning, Julie; Allen, Gemma
Abstract : Introduction/Background: Anaemia is common in patients with cervical cancer. Existing guidelines emphasise the importance of maintaining haemoglobin levels above 120 g/L in cervical cancer patients undergoing chemoradiation. The aim of the study is to evaluate the impact of anaemia on the clinical outcomes in patients with cervical cancer referred for chemoradiation. Methodology: 135 patients (median age was 48 years) with cervical cancer (squamous= 79.3%, Adenocarcinoma= 12.6%, Adenosquamous= 8.1%) referred for radical chemoradiartion between January 2013 and December 2017 were reviewed retrospectively. The FIGO stages for the group were: Ib2 = 11%; II = 42%; III = 39%; IVa =8%. Patients underwent chemoradiation with external beam radiotherapy with concurrent weekly cisplatin for five cycles followed by high-dose-rate brachytherapy. Factors included in the analysis were age, histology, FIGO stage, nodal status, pre-treatment haemoglobin, pre-brachytherapy haemoglobin and post treatment haemoglobin. Results: After a median follow-up of 42 months, the 3 year local failure rate for the whole group, pre-treatment Hb < 120 g/L and pre-brachytherapy Hb < 120 g/L was 9%, 15% and 22% respectively. The 3 year overall survival rate was 72%, 65% and 49% respectively. 52 patients (38.5%) had anaemia at presentation (Hb < 120 g/L). There was significant association between anaemia and younger age, more advanced stage and lymph node involvement. Anaemia was corrected by blood transfusion and/or ferric carboxymaltose. The pre-brachytherapy Hb level had the strongest impact on both local failure and survival. The post-treatment Hb level did not have an impact on the outcomes. Conclusion: Anaemia in patients with cervical cancer undergoing chemoradiation was a strong prognostic factor for local control and survival. The pre-brachytherapy Hb level had the strongest impact indicating the benefit from correcting the anaemia before treatment and maintaining the Hb level above 120 g/L during the treatment.